Antibody drug conjugates (ADC) and bispecific antibodies in oncology - report of the 2022 Saint Louis day - Ranchon, Florence; Chatelut, Étienne; Lambert, Juliette; Sesques, Pierre; Thibault, Constance; Madelaine, Isabelle; Rioufol, Catherine; Diéras, Véronique; Cazin, Jean-Louis (Bulletin du cancer, 2023)
Antibody Drug Conjugates (ADC) and bispecific antibodies are booming and were the subject of the scientific event proposed by the French Society of Oncological Pharmacy, October 13, 2022. An ADC is composed of the antibody targeting a receptor expressed on the tumor cell, the spacer making it possible to attach the cytotoxic to the antibody and to control its distribution in the body, and the cytotoxic. Therapeutic antibodies, monoclonal and conjugated, have particular pharmacokinetics. Unlike monoclonal antibodies for which the standard dose is most often fixed, this is expressed in mg/m (or mg/kg) and capped at 2m (or 100kg) for conjugates. The linked cytotoxics are powerful cytotoxics: mitotic spindle poisons (emtansine, monomethyl auristatin E or vedotin), topoisomerase I inhibitors (deruxtecan, SN 38) or antibiotics (ozogamicin). In senology, trastuzumab deruxtecan (anti-HER2) and sacituzumab govitecan (anti-Trop 2) are now modifying treatment standards for patients with metastatic breast cancer, respectively HER2 3X or HER2 low and triple negative. In metastatic bladder cancer, enfortumab vedotin (anti-nectin 4) is positioned as the 2nd line of treatment. Bispecific antibodies, on the other hand, are able to target two epitopes, an antigen specific to a tumor cell and one to an immune cell, allowing a bridge between the killer immune cells and the tumor cells. For lymphoma proliferation, many bispecific antibodies are in development. The most advanced are glofitamab, epcoritamab and mosunetuzumab, which target the CD20 of B lymphocytes and the CD3 of T lymphocytes. Bispecific antibodies are also emerging in the treatment of myeloma with teclistamab and elranatamab (anti-CD3 and anti-BCMA) or talquetamab (anti-GPRC5D and anti-CD3). Conjugated antibodies, and more recently bispecific antibodies, are potential game changers in cancer treatment and researchs are needed to improve their efficacy and safety.